New species of Luperosaurus (Squamata: Gekkonidae) from the Crocker Range Park, Sabah, Malaysia (Borneo) - Das, I.; Lakim, M.; Kandaung, P. (Zootaxa, 2008)
A new species of Luperosaurus is described from the Crocker Range Park, Sabah, northern Borneo (East Malaysia). The new species is known only from the holotype (SVL 34.7 mm), and is diagnosable from congeneric species by possession of the following combination of characters: body robust; head narrower than body; auricular opening oval-squarish; subrictal tubercles present; two intersupranasals contacting rostral; rostral in contact with nares; nine supralabials at midorbital position; 14/15 (R/L) supralabials to posterior edge of orbit of eye; 11 infralabials to posterior edge of orbit; dorsal body scales rounded, convex and granular; ca. 104 dorsal scale rows; 45 ventral scale rows; ca. 149 midbody scale rows; 1–3 anteriormost chin scales subequal, larger than those to their posterior; ventrolateral body tubercles spinose; three distal scansors deeply notched; tail fringe with distinct serrations; and pale rounded spots on middorsum.